Anomalous enhancement of the sheet carrier density beyond the classic limit on a SrTiO(3) surface - Kumar, Neeraj (Sci Rep, 2016)
Electrostatic carrier accumulation on an insulating (100) surface of SrTiO(3) by fabricating a field effect transistor with Parylene-C (6 nm)/HfO(2) (20 nm) bilayer gate insulator has revealed a mystifying phenomenon: sheet carrier density [Image: see text] is about 10 times as large as [Image: see text] ([Image: see text] is the sheet capacitance of the gate insulator, V(G) is the gate voltage, and e is the elementary charge). The channel is so clean to exhibit small subthreshod swing of 170 mV/decade and large mobility of 11 cm(2)/Vs for [Image: see text] of 1 × 10(14) cm(−2) at room temperature. Since [Image: see text] does not depend on either V(G) nor time duration, [Image: see text] beyond [Image: see text] is solely ascribed to negative charge compressibility of the carriers, which was in general considered as due to exchange interactions among electrons in the small [Image: see text] limit. However, the observed [Image: see text] is too large to be naively understood by the framework. Alternative ideas are proposed in this work.